EVALUATION OF DOSHA DUSHTI, SROTO DUSHTI & QUALITY OF LIFE IN LONG COVID-19 SUBJECTS – AN OBSERVATIONAL STUDY - VYSHNAVI R; SUBASH CHANDRA BOSE. M (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2025)
SARS-COV-2 has resulted in a global pandemic and an unprecedented public health crisis. It has infected more than 75 million people worldwide. Clinical features vary from a mild asymptomatic state to a severe state with respiratory dysfunction, thrombotic complication and multi-organ failure. Recent literature suggests the emergence of a novel syndrome known as “Long COVID/Post-COVID-19 Syndrome”, a term used to describe a diverse set of symptoms that persist after a diagnosed COVID-infection. Recently, National Institute for Health and Care Excellence(NICE) guidelines effectively defined, ‘Post-COVID-19 syndrome’ as a persistence of symptoms beyond 12 weeks from the date of onset and are not explained by an alternative diagnosis. Ongoing symptomatic COVID-19 is defined as signs and symptoms that persist between 4 and 12 weeks from the onset of the infection. The term “Long-COVID-19” includes both ongoing symptomatic COVID-19(4-12 weeks) and post-COVID-19 syndromes (>12 weeks). Presentation can vary greatly between individuals, making diagnosis and treatment challenging. Management of patients with ‘Long-COVID-19’ should include a multidisciplinary team. There is no disease which manifest without undergoing vitiation of dosha.  The kupita dosha depending upon the nature of hetu, travels to various parts of the body and produces variety of diseases. Disturbance in dosha leads to sammoorchana with dushya and takes sthanasamsraya which results in disease manifestation. Quality of life assessments are used in broad ranging ways. It rays light on the assessment of disease prognosis. It is quintessential to evaluate dosha and srotas in understanding the samprapti of a disease. Hence the assessment of dosha and sroto dushti and QOL is carried out in Long-COVID-19 subjects to evaluate the extent of involvement, which is further helpful in planning treatment protocols